2008
DOI: 10.1007/s11632-008-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Nest-cavity characteristics of the Great Spotted Woodpecker Dendrocopos major in shelter plantations of west Inner Mongolia

Abstract: The Great Spotted Woodpecker Dendrocopos major (L.), one of the natural predators of Anoplophora glabripennis (Motsch.) (Coleoptera: Cerambycidae), is resident to Wulate Qianqi County of the Inner Mongolia and widely found in shelter plantations. In August 2005 and 2006, 174 and 153 nest-cavities of Great Spotted Woodpeckers were found respectively in Wulate Qianqi County and 22 breeding nest-cavities were investigated in 2007. The results showed that mostly willow species were selected for nesting by the Grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Two species which form physical supports of predilection to excavate nest cavities in Levaillant's woodpecker (Badis and Hamdi 2022). They offer optimal and safe conditions for the implementation of cavities such as the low ammability and consistency of cedar woods, as well as its tolerance to various water and climatic stress (Valette 1990 In woodpeckers, the dimensions, and shapes of the entrances to their nest cavities are adapted according to body size (Kerpez and Smith 1990; Kosinski and Ksit 2007; Wan et al 2008). In Levaillant's Woodpecker in the Aures Mountains, the surveys carried out as part of this study show that the entrances are mostly round (94.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Two species which form physical supports of predilection to excavate nest cavities in Levaillant's woodpecker (Badis and Hamdi 2022). They offer optimal and safe conditions for the implementation of cavities such as the low ammability and consistency of cedar woods, as well as its tolerance to various water and climatic stress (Valette 1990 In woodpeckers, the dimensions, and shapes of the entrances to their nest cavities are adapted according to body size (Kerpez and Smith 1990; Kosinski and Ksit 2007; Wan et al 2008). In Levaillant's Woodpecker in the Aures Mountains, the surveys carried out as part of this study show that the entrances are mostly round (94.2%).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there seems to have been no studies showing the adaptive advantages of particular nest orientations, but it is believed that they occur. Landler et al (2014) included data from 12 studies on Great Spotted Woodpeckers and all but three of these studies found random orientation, the exceptions being studies in Great Britain (Tracy 1938), China (Wan et al 2008) andPoland (Hebda 2009). In the present study of White-backed Woodpecker cavities across Hungary, orientation was non-random with a general alignment and southerly orientation of entrances prevailing.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed tree planting and the conservation of deadwood have been shown to encourage woodpeckers to move into forested areas . The physical characteristics of nest holes have also been identified in order to produce suitable artificial nest holes or nest boxes for woodpeckers, and have also been successfully used to encourage woodpecker predation of Anoplophora …”
Section: Predatorsmentioning
confidence: 99%
“…The biological control prospects for predators are more promising, as both woodpecker species that predate on A. glabripennis are native in Europe and would only require measures to encourage their establishment in an area of infestation, such as artificial nest boxes and changes in management of woodland to allow more deadwood and more diversity of tree species …”
Section: Prospects For Biological Control Agents In Europementioning
confidence: 99%